MY SAY: Envisioning Asia 2060 - Abd Razak, Dzulkifli (2010)
A group of experts met last week at Tamkang University Graduate Institute of Future Studies in Taipei to discuss "Global Transitions and Asia 2060". The broad focus of the meeting, co-hosted by the US-based Foundation for the Future was on three areas — climate, political economy and identity. The writer gave the keynote address.